PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA BOOKLET DIET GINJAL TERHADAP PENGETAHUAN DAN SIKAP PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD DR. PIRNGADI KOTA MEDAN - Dalimunthe, Dina Yusdiana (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2016)
Kidney diet is a diet or determining of diet for the patient with kidney disease. This knowledge is very important to control the diet of chronic kidney disease early. The objective of this research is to know the effect of health education with the booklet media of kidney diet to the knowledge and attitude of patient with chronic kidney disease at Hemodialysis Room Dr. Pirngadi Hospital Medan. Researchers used quantitative research with Quasy Experimental Design with One Group Pretest – Posttest design. The population is the patient with chronic kidney disease at Hemodialysis Room Dr. Pirngadi Hospital Medan in 2014 for 1872 persons with the average number in month is 156 persons. The sample can be taken with the confidential level 15% of the total monthly population, so the sample is 35 persons. The result of research to 35 respondent indicates that before the health education with the booklet media of kidney diet, the number with good knowledge is 5 persons (14.2%), sufficient for 15 persons (42.9%), less for 15 persons (42.9%), and after the health education with the booklet media of kidney diet, there is increasing of knowledge of patient with the good knowledge is 20 persons (57.1%), sufficient for 12 persons (34.3%), and less for 3 persons (8.6%). Based on attitude before the health education with the booklet media of kidney diet, respondent with positive attitude is 14 persons (40%), negative for 21 persons (60%). After the health education with the booklet media of kidney diet, there is increasing of attitude of patient with the positive attitude is 29 persons (82.9%) and negative for 6 persons (17.1%). And by statistical test of Paired T-Test indicates that p = 0.000 < 0.05. It concluded that there is the effect of health education with the booklet media of kidney diet to the knowledge and attitude of patient with chronic kidney disease at Hemodialysis Room Dr. Pirngadi Hospital Medan.Keywords: Kidney Diet, Knowledge and Attitude, Health Education